Gate tunable giant anisotropic resistance in ultra-thin GaTe - Hanwen Wang (Nature Portfolio, 2019)
Some atomically thin crystals feature crystallographic anisotropy, but demonstrations of electrical anisotropy are scarce. Here, the authors show that the electrical conductivity of few-layered GaTe along the x and y directions can be widely gate tuned up to 103, and demonstrate anisotropic non-volatile memory behavior.